Você está na página 1de 53

 

 

 

 

 

 

 

r 1 r 2 R

 

r 1 r 2

 

r = α ±

 

 

 

 

 

 

 

 

 

F = − k.x P = m.g = m.a

F = k.x

P = m.g = m.a

m.a = kx

a = dv dt

=

d 2 x dt 2

m.x˙ + k.x = 0

x n (t) = G(x(t), x 1 (t), x 2 (t),

, x n1 (t)

a n .y n (t) + a n1 (t).y n1 (t) + a 1 (t).y 1 (t) + a 0 (t).y(t) = F (t)

a 1 (t).y 1 (t) + a 0 (t).y(t) g(t)

a 1 (t)

y 1 (t) + p(t).y(t) = f (t)

p(t) = 0

y(t) = f(t)

dx dy y(t)dt = f (t)dt

y(t) = f (t)dt + C

f (t) = 0 p(t) = a

y(t) = a.y(t) = 0

dx dy y(t) + a.y(t) = 0

y(t) = C.e a.t

p(t) = a

y (t) + a.y(t) = f (t)

d

dt (e at .y(t)) = a.e at .y(t) + e at y (t) = e a.t (y(t) + a.y (t))

e at

e a.t (y (t) + a.y(t)) = f (t).e a.t

dt d (e a.t .y(t))

=

e a.t .f (t)

d

dt (e a.t .y(t))dt = e a.t .f (t)dt

e a.t .y(t) = e a.t .f (t)dt

+ C

y(t) = e a.t e a.t f (t)dt +

C.e a.t

e a.t

y (t) + p(t).y(t) = f (t)

d

dt (µ(t).y(t) = µ (t).y(t) + µ(t).y (t)

µ (t).y(t) + µ(t).y (t) = µ(t).f (t)

µ(t)

y (t) + µ µ(t) (t) .y(t) = f (t)

y (t) + p(t).y(t) = f (t) p(t) = µ (t)

µ(t)

p(t)dt =

µ(t)

µ(t) dt

µ (t) dt = ln µ(t) + C

µ(t)

e p(t)dt = e ln µ(t)+C = µ(t)

µ(t)

y (x) =

g(x)

1

h(y(x)) = g(x). h(y(x)

h(y(x)).y (x) = g(x)

h(y(x)).y (x)dx = g(x)dx

H(y(x)) h(y(x))

dy

dx

[H (y(x)).y (x) = h(y(x)).y (x)

(4)

h(y(x)).y (x)dx = g(x)dx

H(y(x)) = G(x) + C

h(y).y (x) = g(x)

h(y). dx dy dx = g(x)dx h(y)dy = g(x)dx

y = 6xy

1 dy

y . dx

= 6x, y

= 0.

1

y dy = 6xdx

2

ln y = 6 x 2

+ C

y(x) = c 1 .e 3x 2

y(x)

y = f( x ))

y

y = f(

y

x )

(5)

v(x) = y(x)

x

x.v(x) = y(x)

v(x) = x.v (x) = y (x)

(5)

dv

v(x) + x.v (x) = f (v) x. dx = f(v) f(x)

f(v)

v v(x)dx f(v) v(x) = dx

x

2xy dx = 4x 2 + 3y 2

dy

2xy

dy

dx =

4x 2

2xy + 2xy

3y

2

dy dx = 2x

y

3y

+ 2x

f ( x )

v

y

y

x = v x.v = v

v + x.v = y

1

v + x.v = 2( v ) + 3

2 v

x.v =

2

v + 2 3 v v

x.v =

2

v

1

+ 2 v

x

dx = 4 + v 2

dv

2v

2v

v 2 dv =

4 +

dx

x

u = 4 + v 2 du = 2vdv

du

u

=

ln(4 + v 2 )

ln(4 + v 2 ) = ln(|x|) + C

x

y

F (x, y) = C

dF

dy

dy

dx . dx + dx = 0

dF = dF dx + dF dy

dx

dy

F x y

dF

dx

= F x = M (x, y), dF dy

= F y = N (x, y)

M (x, y)dx + N (x, y)dy = 0

F (x, y) = C

F x = M F y = N ω F x y = F y x M y = M x M y = M x

M (x, y) N (x, y)

ω : (x, y) : a < x < b, c < y < d M (x, y)dx +

N (x, y)dy = 0 M y = N x

ω

F (x, y) = C (I) F x = M (I)

(II) F y

= N

F (x, y) = F x dx = M (x, y)dx + g(y)

g(y) F y = N

F y =

y M (x, y)dx + g (y) = N (x, y)

g (y)

g (y) = N (x, y) y M (x, y)dx

x

g (y) = N (x, y) y M (x, y)dx 0 =

x N (x, y)

∂x

y M (x, y)dx

x M (x, y)dx = M (x, y) N x = M y

N x

= M y x y

(cos x + ln y)dx + ( x + e y )dy = 0

y

M (x, y) N (x, y)

M y =

1

y = N x = 1

y

F (x, y) = C, comF x = M, F y = N

M

F x dx = (cos x + ln y)dx + g(y) = senx + x ln y + g(y)

F y = 0 + x + g (y)

y

M N

( x + g (y)) = ( x + e y )

y

y

g (y) = e y g(y) = e y + C

F (x, y) = senx + x ln y + e y = C

(cos x + ln y + 0)dx + ( x + e y )dy = 0

y

∂F = F ∂x

+ ∂F

∂y

y = f (x, y) y(a) = b)

R = α x β, c y d R 2 R

f (x, y) R y(x)

y R y(x)

(a, b)

y ) R y ( x ) y R y ( x ) ( a, b

(a, b) y(x)

y = x 2 y(1) = 1

f (x, y) = y 2 R

f x = 2y R

dy

y 2

= dx

y 1 = C x

y(x) =

1

C x

1 = y(1) =

1

1 , logoC = 2

C

y(x) =

1

2 x

a(x).y + b(x).y + c(x).y = d(x)

A.g + B.g + C.G = 0

C 1 g

A.C 1 .g + B.C 1 .g + C.C 1 .g

C 1 (A.g + b.g + C.g)

C 1 .0 = 0 C 1 .g(x)

h(x) g(x) + h(x)

A.(g + h) + B.(g + h) + C(g + h)

A.g + A.h + B.g + B.h + C.g + C.h

(A.g(x) + B.g(x) + C.g(x)) + A.h(x) + B.h(x) + C.h(x)

y = e r x

y = e r x

y = r.e r x

y = r 2 .e r x.

r 2 .e r x + 5.r.e r x + 6.e r x = 0

r = 2 r = 3

y(x)

y 1 =

e 2x

y 2 = e 3x

C 1 C 2

y 1 =

C 1 .e 2x

y 2 =

C 2 .e 3x

y 1 y 2 L(y 1 ) =

y

1

+ p.y 1 + q.y 1 = 0 y 2

L(y) = y + p(t).y + q(t).y = 0

c 1 ; y 1 +c 2 .y 2

L(y) = y + p(t).y + q(t).y

y 1 y 2

W(y 1 , y 2 ) =

y 1

y

(1)

1

y 2

y

(1)

2

W(y 1 , y 2 ) = y 1 y 2 1) y 1 1)y 2 4

(

(

t 0 y(t 0 ) = y 0 y (t 0 ) = y (t 0 ) c 1 c 2 y = c 1 y 1 (t)+c 2 y 2 (t)

y 1 , y 2 , y 3 ,

)

r 1 r 2 R

y(x) = c 1 .e r 1 x + c 2 .e r 2 x

c r y(x 0 ) = y 0 y(x 1 ) = y

1

d 2 x

dx 2

+

4 dx dy , y(0) = 1, y (0) = 2

λ

λ 2 + 4λ 2 = 0

λ

λ = 2 ± 6

y(x) = c 1 .e 2+ 6x + c 2 .e 2 6x

y(0)

y(0) = c 1 + c 2

y(x)

y(x)

y (0) = (2 + 6).c 1 + (2 6).c 2

y(0) = c 1 + c + 2

y (0) = (2 + 6).c 1 + (2 6).c 2

c 1 =

2

1

2 ec 2 =

6 +

1

2

2

6

y(x) =

2

6 +

2 .e 2+ 6x + 1 2 2 6 .e 2 6x

1

r 1 r 2

d 2 y

dx 2

+

6 dx dy 9y = 0

(λ 2 + 6λ 9) = 0 (λ 3) 2 = 0

y 1 = e 3x y 2 (x)

v(x) y(x)

y 2 (x) = e 3x .v(x)

d

2 y 2

dx

2

=

dy

2

dx

2

dv

= e 3x . dx 3.e 3x .v

e 3x . d 2 v + 6.e 3x dx + 9.e 3x .v

dx

dv

(e 3x .

d 2 v

dx 2

+

(λ 2 + 6λ 0) = 0

dv

dv

6.e 3x . dx + 9e 3x .v) 6(e 3 x. dx + 3e 3x .v) + 9e 3x .v = 0

e 3x .

d 2 v dx 2 = 0

e 3x .

d 2 v

dx

2

dx = 0dx

dv

dx = c 1

x v

dv

dx dx = cdx

v(x) = c 1 .x + c 2

y 2 (x) = e 3x .(c .x + c